A Case of Perforated Sigmoid Diverticulitis in Which Gram Staining of Ascitic Fluid Was Useful for Diagnosis. (4th March 2014) - Tsuchida, Junko; Fujita, Shouhei; Kawano, Fumihiro; Tsukamoto, Ryoichi; Honjo, Kunpei; Naito, Shigetoshi; Ishiyama, Shun; Miyano, Shozo; Machida, Michio; Kitabatake, Toshiaki; Fujisawa, Minoru; Kojima, Kuniaki; et al.
Abstract : An 85-year-old woman was admitted to our hospital for steroid therapy for relapsing nephrotic syndrome. During hospitalization, she complained of sudden epigastric pain at night. Although there were signs of peritoneal irritation, CT showed a large amount of ascitic fluid, but no free intraperitoneal gas. Gram staining of ascitic fluid obtained by abdominal paracentesis showed Gram-negative rods, which raised a strong suspicion of gastrointestinal perforation and peritonitis. Therefore, emergency surgery was performed. Exploration of the colon showed multiple sigmoid diverticula, one of which was perforated. The patient underwent an emergency Hartmann's procedure. Imaging studies failed to reveal any evidence of gastrointestinal perforation, presenting a diagnostic challenge. However, a physician performed rapid Gram staining of ascitic fluid at night when laboratory technicians were absent, had a strong suspicion of gastrointestinal perforation, and performed emergency surgery. Gram staining is superior in rapidity, and ascitic fluid Gram staining can aid in diagnosis, suggesting that it should be actively performed. We report this case, with a review of the literature on the significance of rapid diagnosis by Gram staining.